2015
DOI: 10.3892/etm.2015.2962
|View full text |Cite
|
Sign up to set email alerts
|

Levels of interleukin-6, superoxide dismutase and malondialdehyde in the lung tissue of a rat model of hypoxia-induced acute pulmonary edema

Abstract: Abstract. The present study aimed to investigate the levels of malondialdehyde (MDA), superoxide dismutase (SOD) and interleukin (IL)-6 in the lung tissue of a rat model of acute pulmonary edema induced by acute hypoxia, and its pathophysiological significance. A total of 48 adult Wistar rats were randomly divided into group A, a normal group; group B, a model of acute pulmonary edema induced by hypoxia for 24 h; group C, a model of acute pulmonary edema induced by hypoxia for 48 h; and group D, a model of acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…IL-8 functions include chemotaxis and activation of neutrophils, as well as chemotaxis of basophils, T lymphocytes, and other inflammatory cells ( 4 ). Decreased antioxidant capacity and increased free radical levels have been implicated in the pathological changes associated with pulmonary diseases ( 5 ). Superoxide dismutase (SOD) is a critical antioxidant that can effectively eliminate superoxide anions and protect cells from oxidative damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-8 functions include chemotaxis and activation of neutrophils, as well as chemotaxis of basophils, T lymphocytes, and other inflammatory cells ( 4 ). Decreased antioxidant capacity and increased free radical levels have been implicated in the pathological changes associated with pulmonary diseases ( 5 ). Superoxide dismutase (SOD) is a critical antioxidant that can effectively eliminate superoxide anions and protect cells from oxidative damage.…”
Section: Introductionmentioning
confidence: 99%
“…Proof of the efficacy of angiotensin-( 1 7 ) [Ang-(1–7)] as a novel therapeutic agent for many diseases has been revealed in preclinical studies. Angiotensin-converting enzyme 2 (ACE-2) degrades Ang II by removal of a single amino acid to generate the heptapeptide Ang-(1–7).…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant capacity reduction and free radical levels elevation have been reported to be involved in the pathological changes of pulmonary diseases [ 30 ]. The effect of SIN on oxidative stress was determined by detecting MDA content, SOD activity, and CAT level in lung tissues.…”
Section: Discussionmentioning
confidence: 99%
“…All three studies reported that IL-6 treatment resulted in improved or normalized nerve function and/or morphology. While none of these studies reported the corresponding plasma levels of IL-6 following administration, there are literature reports to establish normal rat plasma IL-6 levels to be 50–100 pg/mL ( 62 64 ), and after a single intraperitoneal injection of 25 µg/kg plasma IL-6 levels peaked at ~5,500 pg/mL dropping off to near baseline within 4 h ( 65 ). Taken together, the data demonstrate a transient 50- to 100-fold increase in IL-6 following a single dose administration may represent therapeutic range.…”
Section: Preclinical Studies: Il-6 Administration In Rodent Models Ofmentioning
confidence: 99%